Peningkatan Pemahaman Dunia Kerja dan Kompetensi Lulusan SMK di Era Industri 4.0 - Alfizi Alfizi; Yadi Fakhruzein Terang Jaya (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
The major transformation occurring in the era of the Industrial Revolution 4.0 has significantly altered the characteristics of the world of work, particularly in terms of job structures, recruitment patterns, and the competencies required of the workforce. This condition has a direct impact on graduates of vocational education, including Vocational High Schools (Sekolah Menengah Kejuruan/SMK), which are projected to supply job-ready human resources. This Community Service Program (Pengabdian kepada Masyarakat/PKM) aims to strengthen SMK students’ understanding of labor market dynamics and the key competencies needed to face the challenges of Industry 4.0. The program was implemented at SMK Ma’arif NU Bobotsari using an educational and participatory approach through interactive lectures, discussions, and motivational reinforcement. The results indicate an improvement in students’ understanding of changes in the world of work, increased awareness of the importance of both technical and non-technical competencies, and initial readiness in career planning. This activity provides a tangible contribution to enhancing the readiness of SMK graduates and strengthening the linkage between vocational education and industry needs. Keywords: Industry 4.0, world of work, SMK graduate competencies, hard skills.